Estruturação de capital nas empresas de Cabo Verde - Lima, Lia Jéssica Delgado Brito (2022)
The capital structure represents one of the concepts most addressed in corporate finance, both nationally and internationally, however, no studies on Cape Verdean companies are known, which makes the present work relevant and innovative. The concept of capital structure refers to the decisions that companies have to make as to the sources of finance to turn to, whether to use more outside capital or more equity. Thus, the optimal capital structure is considered as one of the biggest challenges of financial management, where the focus is to lower the total cost of financing as much as possible while simultaneously increasing the value of the investment to the equity holders or managers. There are several theories that try to explain these structural decisions of companies. The most studied being the trade-off theory and the pecking order theory. The first consists of the existence of an optimal capital structure for each class of equivalent income, where there is a ratio between own and other capital. The second, also known as the funding sources hierarchy theory, argues that companies first choose to use internally generated funds (self-financing) to finance a project, secondly use debt relief (third party financing) and last resort to the issuance of new shares. Based on these theories and the capital structure determinants, this paper aims to investigate which theories and determinants influence the capital structure of Cape Verdean companies. To this end, financial information will be used from a set of Cape Verdean companies, obtained by convenience and applied linear regression. The results indicate that tangibility positively influences companies' indebtedness. This behavior may indicate that companies can follow either the trade-off theory or the pecking order theory during this period.